Shp-1 regulates the activity of low-affinity T cells specific to endogenous self-antigen during melanoma tumor growth and drives resistance to immune checkpoint inhibition - Joseph G Matous; Jeremy P Snook; Nico A Contreras; Andrew G Ramstead; Krystal R Charley; Elizabeth M Kolawole; Jacob N Kisiolek; Kaitlyn A Flint; Ashleigh J Soedel; Breyana Robinson; Anaiya B Mendoza; Yohichi Kumaki; et al. (Journal for ImmunoTherapy of Cancer)
Background The presence of activated CD8 T cells in the tumor microenvironment is correlated with an effective immune response to immune checkpoint inhibitor (ICI) therapy. However, ICI predominantly targets high-affinity T cells, which may be less abundant in tumors with few neoantigens. Targeting the intracellular phosphatase Src homology region 2 domain-containing phosphatase-1 (Shp-1) in combination with ICI lowers the T cell activation threshold and enhances the ability of low-affinity T cells to mount a productive antitumor response.Methods In this study, we sought to determine whether temporal inhibition of Shp-1 during active tumor growth could rescue the activity of low-affinity T cells specific for endogenous self-antigens. To address this question, we implanted Yale University Mouse Melanoma (YUMM) tumor cell lines into WT mice and, on tumor establishment, administered an inhibitor of Shp-1 (TPI-1) with or without ICI treatment. We analyzed treatment-dependent changes in the immune infiltrate in the tumor via flow cytometry, major histocompatibility complex (MHC) tetramer-mediated detection of tyrosinase-related protein 2 (TRP-2)180–188-specific T cells and a micropipette-based two-dimensional affinity assay to measure the T cell receptor (TCR) affinity.Results Administration of ICI and a Shp-1 inhibitor to mice with established YUMM tumors, but neither agent alone, resulted in a significant delay in tumor growth and an increased frequency of CD8 tumor-infiltrating T cells with enhanced effector and reduced exhaustion characteristics. In particular, combined treatment increased the frequency of CD8 T cells specific for the MHC Class I-restricted tumor self-antigen TRP-2180–188. We found that the increase in effector T cells was almost entirely due to an increase in T cells with very low TCR affinity.Conclusions We conclude that approaches for altering TCR signaling threshold are effective in enhancing the antitumor response of low-affinity T cells specific for endogenous self-antigens in settings of ICI resistance and/or where neoantigens are not available to drive antitumor responses.